RESISTANCE TRAINING HEMODYNAMIC IMPROVEMENT CARDIOVASCULAR IN THE ELDERLY: INVOLVING AUTONOMIC BALANCE AND IMMUNE SYSTEM - Wolpp, E. Teodora Rachid; Silva-Reis, Anamei; Maia, Meiry De Souza Moura; Vieira, Rodolfo de Paula (CIPEEX, 2025)
The study evaluated the effects of resistance training on the cardiovascular and immunological health of the elderly. Sixty-nine participants were randomly divided into a control group and a training group, which performed resistance exercises three times a week for 12 weeks. The pre- and post-training assessments included measurements of heart rate, blood pressure, and hemodynamic analysis by impedance cardiography. Inflammatory biomarkers and functional capacity were also analyzed. The results showed that resistance training significantly improved various cardiovascular parameters, such as increased stroke volume, cardiac output, and heart rate variability, as well as reduced systemic vascular resistance. There were also improvements in respiratory muscle strength and functional capacity, with an increase in the number of repetitions in the sit-to-stand test and the elimination of oxygen desaturation during the test. Additionally, the training promoted positive effects on the immune system, reducing levels of interleukin 6 and tumor necrosis factor alpha, and increasing interleukin 10 and Klotho. It is concluded that resistance training can be an effective intervention to improve cardiovascular hemodynamics, autonomic balance, and immune response in the elderly, as well as enhance muscle strength and functional capacity, thereby promoting healthier aging.